Stall behavior curved planform wing analysis with low reynolds number on aerodynamic performances of wing airfoil eppler 562 / Setyo Hariyadi S.P. ... [et al.] - S.P, Setyo Hariyadi; Junipitoyo, Bambang; Ali, Sutardi; Widodo, Wawan Aries (Universiti Teknologi MARA, 2022)
On airplanes and UAVs, a stall is something that is always attempted to avoid. Stalling can also be aided by the employment of planform wings with varying geometry. Curved wing variations are often used in UAV applications, especially at low Reynolds numbers. This study discusses stall behavior on rectangular, elliptical, semi-elliptical, and Schuemann wings. Numerical simulations were performed using the turbulent k-ω SST model using Ansys Fluent 19.1. The airfoil used in this study was Eppler 562 at Reynolds number 2.34 x 104. The angles of attack observed were 0o, 2o, 4o, 6o, 8o, 10o,12o, 15o, 17o, 19o, and 20o. The Schuemann wing has the best performance that is indicated by the delaying of the stall point, which is at an angle of attack α = 15o, while the rectangular wing produces the highest lift to drag ratio compared to other planform wings. The confluence of the main flow and backflow forms towards the mid-span as the angle of attack increases. The rectangular wing produces high vorticity in the wingtip area due to the tip- vortex phenomenon, while the elliptical and Schuemann wing in the leading edge area due to the geometry of the leading edge.